Mp Tuning for Internal Model Control 2x2 Multi Input Multi Output (MIMO) System - Dinny Winda Astuti; Juwari Juwari; Renanto Handogo (IPTEK Journal of Proceedings Series, 2014)
IMC is a type of model based control that compensates time delay in the process. The controller tuning is quite simple in case of no-error in the model, otherwise it will be a difficult matter. Mp tuning has been considered a tuning for uncertain processes. To extend  IMC to MIMO system, a new method  based on Maximum Peak (Mp) is developed . The present study proposes Maximum Peak  (Mp) tuning for IMC in 2x2  multi input and multi output (MIMO) system. Three particular 2x2 model of distillation colomn are being studied, the best configuration is analyzed by Relative Gain Array (RGA) and Average Dynamic Gain Array (ADGA) method. The tuning method  consists of two main steps: Firstly, determine the worst case of the model uncertainty. Secondly, specify the parameter of set point controller using maximum peak (Mp) criteria.  The effectiveness of Mp tuning for IMC in MIMO system  is  evaluated and compared to Biggest Log Modulus Tuning (BLT) for MIMO-PI Controller, Skogestad Tuning, and Rivera Tuning. Evaluation and comparison  have been done through simulation and the results are satisying.